LOCAL WISDOM: LOCAL RICE EXCELLENCE FROM CREATIVITY OF FARMER BREEDERS: (Case Study of Indramayu Regency, West Java) - Ichdayati, Lilis Imamah (Archives of Business Research, 2019)
Creativity farmer breeders get legal protection through the Constitutional Court of Indonesian Republic Decision No.99/PUU-X/2012 so that the seed and grain farmer breeders creative product can be marketed for their communities. This activity has an economic impact. Therefore the study aims to analyse the benefits of rice farming and to know the content of local wisdom on the application of environmentally friendly rice cultivation and sustainable. The research location in Indramayu with samples farmer breeders in the first 13 districts of local rice production centre using a snowball sampling technique. The data of this research is primary data obtained from an interview with questionnaire guide, during July-August 2016. The analytical tool used is the analysis of income and descriptive analysis related to local wisdom in the cultivation of rice crops in the fields. The results of the research are as follows: (1) Farmer breeders gain a significant advantage because of two things: the cost savings of inputs and able to increase the average rice productivity (2) local wisdom appearing in the institution rice cultivation,for breeder farmers to grow awareness that rice farming in addition to meaningful economic, ecological and social, also means life itself.